GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU LEMBAGA DI MADRASAH IBTIDAIYAH HIDAYATUL ULA PROBOLINGGO - Dien Fauzia Rokhmi; Jadid Khadavi, M.; Khosiah, Nur (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research aims to evaluate the effectiveness of using number bags in improving students'understanding of place value material in class II MI Bustanul Ulum Tempuran. By usingquantitative methods and involving 14 students as the population, data were collected throughtests and documentation. Data analysis was conducted using pretest, posttest, normality test,and N gain test using SPSS 21.0 software. The research results show a significant improvementin material understanding, with an average pretest score of 41.4286 and a posttest score of78.5714. However, the significance of the pretest at 0.208 and the posttest at 0.352 indicatesthat there is still room for further improvement in the effectiveness of using number bags in thiscontext.